PENGGUNAAN MEDIA PAPAN KANTONG PINTAR UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD INPRES MINASA UPA 1 KECAMATAN RAPPOCINI KOTA MAKASSAR - Andi Makkasau; Amir Pada; Latang; Alfina Damayanti (STKIP Subang, 2022)
The research carried out aims to describe the use of smart pocket board media in improving science learning outcomes for fourth grade students of SD Inpres Minasa Upa 1, Rappocini District, Makassar City. This study uses a qualitative approach with the type of classroom action research carried out in 2 cycles. The research subjects were fourth grade teachers and 25 students consisting of 14 male students and 11 female students. Data collection techniques used are observation, documentation, and test techniques.